2020
DOI: 10.1002/ardp.202000254
|View full text |Cite
|
Sign up to set email alerts
|

Concise syntheses and some biological activities of dl‐2,5‐di‐O‐methyl‐chiro‐inositol, dl‐1,4‐di‐O‐methyl‐scyllo‐inositol, and dl‐1,6‐dibromo‐1,6‐dideoxy‐2,5‐di‐O‐methyl‐chiro‐inositol

Abstract: The regio‐ and stereospecific synthesis of O‐methyl‐chiro‐inositols and O‐methyl‐scyllo‐inositol was achieved, starting from p‐benzoquinone. After preparing dimethoxy conduritol‐B as a key compound, regiospecific bromination of the alkene moiety of dimethoxy conduritol‐B and acid‐catalyzed ring opening of dimethoxydiacetate conduritol‐B epoxide with Ac2O afforded the desired new chiro‐inositol derivatives and scyllo‐inositol derivative, respectively. Spectroscopic methods were employed for the characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
(147 reference statements)
0
3
0
Order By: Relevance
“…When the results are compared, unlike CA isoenzyme inhibition profiles, dibromo[1‐{(4‐hydroxyphenyl)ethyl}‐3‐(4‐methylbenzyl)benzimidazol‐2‐ylidene]pyridine palladium(II) ( 1d ) demonstrated the most active inhibition ability toward hCA I and II isoenzyme. It is well‐known that the presence of bromo, [ 63,64 ] phenyl, [ 65 ] benzyl, [ 28 ] pyridine, [ 66 ] and imidazole [ 67 ] groups in the molecules has favor of effects on increasing inhibition effect of AChE and BChE enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the results are compared, unlike CA isoenzyme inhibition profiles, dibromo[1‐{(4‐hydroxyphenyl)ethyl}‐3‐(4‐methylbenzyl)benzimidazol‐2‐ylidene]pyridine palladium(II) ( 1d ) demonstrated the most active inhibition ability toward hCA I and II isoenzyme. It is well‐known that the presence of bromo, [ 63,64 ] phenyl, [ 65 ] benzyl, [ 28 ] pyridine, [ 66 ] and imidazole [ 67 ] groups in the molecules has favor of effects on increasing inhibition effect of AChE and BChE enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…[62] The K i values of the test complexes demonstrated that the most active compound against AChE and BChE was complex 1d (AChE, It is standard for α-Glu with values of it taken from Tariq et al [48] and Klochkov et al [49] are compared, unlike CA isoenzyme inhibition profiles, dibromo[1-{(4hydroxyphenyl)ethyl}-3-(4-methylbenzyl)benzimidazol-2-ylidene] pyridine palladium(II) (1d) demonstrated the most active inhibition ability toward hCA I and II isoenzyme. It is well-known that the presence of bromo, [63,64] phenyl, [65] benzyl, [28] pyridine, [66] and imidazole [67] groups in the molecules has favor of effects on increasing inhibition effect of AChE and BChE enzymes.…”
Section: Enzyme Inhibition Resultsmentioning
confidence: 99%
“…Methylinositol has been used in trials to study the treatment of dementia and Alzheimer's disease [50] .…”
Section: Discussionmentioning
confidence: 99%